Journal of low power electronics and applications (Basel, Switzerland : MDPI Publishing, 2011)
"Journal of Low Power Electronics and Applications (ISSN 2079-9268) is an open access journal which provides an advanced forum for the studies of electronics for low power applications. A special emphasi[s] is made on ultralow power bio-medical applications. It publishes reviews, regular research papers and short communications."
Description based on: Vol. 1, issue 1 (June 2011); title from journal contents screen (publisher's Web site, viewed Nov. 8, 2013).
Latest issue consulted: Vol. 3, issue 4 (December 2013) (viewed Nov. 8, 2013).
Keywords: Power electronics -- Periodicals; Low voltage systems -- Periodicals; Bioelectronics -- Periodicals; Medical electronics -- Periodicals; Bioelectronics; Low voltage systems; Medical electronics; Power electronics; Biomedical Engineering; Electronic journals